2022
DOI: 10.1038/s41541-022-00489-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding drivers of vaccine hesitancy among pregnant women in Nigeria: A longitudinal study

Abstract: Vaccine-preventable-diseases are major contributors to disease burden in Sub-Saharan Africa. There is dearth of knowledge on the drivers of childhood vaccine hesitancy in Nigeria and its impact on coverage. Although understudied, pregnant women are a particularly important vulnerable group and very relevant for childhood vaccination decisions. This study’s aims are to adapt Confidence, Complacency, Constraints, Calculation, and Collective Responsibility, also known as the 5C psychological antecedence scale for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…Compared to their Christian colleagues, Muslim women were found to be less likely to have received TTV. This finding is consistent with earlier findings in Nigeria where it was observed that expectant mothers who were Muslim had the lowest motivation towards vaccinating their unborn children relative to their Christian counterparts [ 23 ]. Reflecting on these findings, Adeyanju et al [ 23 ] and Anyene [ 24 ] opine that heightened vaccine hesitancy among Muslim women may be hinged on issues of trust in vaccines which is further demonstrated in the low uptake of vaccination in a similar religious context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to their Christian colleagues, Muslim women were found to be less likely to have received TTV. This finding is consistent with earlier findings in Nigeria where it was observed that expectant mothers who were Muslim had the lowest motivation towards vaccinating their unborn children relative to their Christian counterparts [ 23 ]. Reflecting on these findings, Adeyanju et al [ 23 ] and Anyene [ 24 ] opine that heightened vaccine hesitancy among Muslim women may be hinged on issues of trust in vaccines which is further demonstrated in the low uptake of vaccination in a similar religious context.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with earlier findings in Nigeria where it was observed that expectant mothers who were Muslim had the lowest motivation towards vaccinating their unborn children relative to their Christian counterparts [ 23 ]. Reflecting on these findings, Adeyanju et al [ 23 ] and Anyene [ 24 ] opine that heightened vaccine hesitancy among Muslim women may be hinged on issues of trust in vaccines which is further demonstrated in the low uptake of vaccination in a similar religious context. In addressing this challenge, it is critical for public health practitioners to work to increase women’s trust in vaccines through their community and religious leadership.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies were done using this model in pregnancy. 136 , 137 Using the 5C model in the pregnant population was a proposal for a vaccine hesitancy intervention in the pregnant population in India. 136 They propose administering the 5C scale at prenatal visits to identify individual patients’ unique behaviors and apply motivational interviewing techniques to address them in real time.…”
Section: Models To Address Vaccine Hesitancymentioning
confidence: 99%
“…A study in Nigeria using the 5C model to understand drivers of vaccine hesitancy for themselves and their children concluded that the 5C model does not perform well in their population. 137 Their intention to vaccinate unborn children was lower if they were Muslims, had lower confidence in the public health system, if husband approval was important, and if they believed in rumor. The authors concluded that the 5C scale needs a revision before being widely used in Nigeria.…”
Section: Models To Address Vaccine Hesitancymentioning
confidence: 99%
“…We exclusively evaluated vaccination reluctance in women in our investigation, therefore the influence of gender on vaccine reluctance could not be identified. However, the female gender has been identified as a significant predictor of vaccine hesitancy in a wide range of investigations ( 37 40 ). Consequently, the coronavirus outbreak has highlighted the necessity for addressing the gender disparity in vaccine aversion, which has mostly been disregarded, except for pregnant cases.…”
Section: Discussionmentioning
confidence: 99%